Methodological aspects of measuring the resistivity of contacts to high-resistance semiconductors - Slipokurov, V.S.; Dub, M.M.; Tkachenko, A.K.; Kudryk, Ya.Ya. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
Proposed has been the method of formation a thermally stable ohmic contact to the diamond without high-temperature annealing with the resistivity ~50 to 80 Ohm∙cm² when Rs = 3∙10⁷ Ohm/ eing based on the analysis of correlation dependence between the resistivity of contact and that of semiconductor for the unannealed sample and the sample after rapid thermal annealing it has been shown that variation of the contact resistance on the plate is related with that of semiconductor and may be caused by inhomogeneity of the dopant distribution.